2013
DOI: 10.3148/74.3.2013.138
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns of Female University Students: With Nutrition Education

Abstract: Dietary patterns were examined in a convenience sample of 36 female University of Alberta students, all of whom had completed at least one nutrition course. Data from a validated food frequency questionnaire were used to determine if students had a dietary pattern similar to that recommended in Eating Well with Canada's Food Guide (EWCFG) or by the Traditional Healthy Mediterranean Diet Pyramid (THMDP), as measured using a Mediterranean Diet Quality Index Score. No student consumed the THMDP minimum number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Yet, other studies found that both genders had low intake of fruits and vegetables [17,40]. Studies of females only also found low intake of fruits and vegetables by most, and the need to improve diet quality [24,31,36,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, other studies found that both genders had low intake of fruits and vegetables [17,40]. Studies of females only also found low intake of fruits and vegetables by most, and the need to improve diet quality [24,31,36,41].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies report that women have healthier eating habits than men [38,51], but others have found no differences between men and women [17,40,48]. Still, regardless of sex, university students' intake of fruits and vegetables remains low [17,24,31,36,40,41,47,51].…”
Section: Resultsmentioning
confidence: 99%
“…Dietary patterns of 36 female students from the University of Alberta, who had completed at least one nutrition course, were compared with the patterns proposed by Eating Well with Canada's Food Guide (EWCFG) or by the Traditional Healthy Mediterranean Diet Pyramid, using the MDQIS . Results revealed that no student consumed the MD's minimum number of portions of legumes, seeds, and nuts, of olive oil or whole grains.…”
Section: Can We Increase Familiarity With the Md?mentioning
confidence: 99%
“…Nutrition education alone may be insufficient to ensure optimal dietary patterns among female university students. The methodology reported in this study presented a novelty in assessing whether dietary patterns resemble MD or EWCFG …”
Section: Can We Increase Familiarity With the Md?mentioning
confidence: 99%
“…Despite initiatives like the CFG, obesity rates in Canada remain high and consumption of healthy foods like vegetables and fruit appears to have declined (Statistics Canada, 2015). Even though the CFG is intended to be only one among many approaches to addressing the complex problem of obesity and diet-related chronic diseases, low compliance rates with the CFG suggest its role has been minimal (Allen, Taylor, Rozwadowski, Boyko, & Blackburn, 2011;Fowler, Evers, & Campbell, 2012;Johnson-Down & Egeland, 2010;Rossiter, Evers, & Pender, 2012;Strawson et al, 2013). Mathe et al (2015) demonstrated that compliance with the CFG is low despite the fact that many Canadians are aware of the CFG and its specific dietary recommendations, while Abramovitch et al (2012) demonstrated that Canadians' misperceptions of some aspects of the CFG, namely, the serving sizes, may actually result in overconsumption of food.…”
Section: Prior Research On Dietary Guidelinesmentioning
confidence: 99%